FORMULATION, OPTIMIZATION AND EVALUATION OF ENROFLOXACIN SOLID LIPID NANOPARTICLES FOR SUSTAINED ORAL DELIVERY - P, Senthil Kumar; A, Arivuchelvan; A, Jagadeeswaran; N, Subramanian; C, Senthil Kumar; P, Mekala (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The objective of the present study was to formulate and evaluate enrofloxacin SLNs using a hot homogenization coupled with ultrasonication method. The SLNs were prepared using tripalmitin as lipid carrier, tween 80 and span 80 as surfactants and poly vinyl alcohol (PVA) as a stabilizer. The influence of factors such as concentration of lipid carrier, composition and concentration of surfactant on the particle size were investigated to optimize the formulations. The optimized SLNs formulations were utilized to entrap 0.1% enrofloxacin and characterized for particle size, polydispersity index, zeta potential (using dynamic light scattering), shape (using atomic force microscopy and transmission electron microscopy), drug encapsulation efficiency (using by dialysis and ultracentrifugation methods), and in vitro drug release (using by dialysis). The prepared SLNs were analyzed by FT-IR spectroscopy to confirm the cross-linking reaction between drug, lipid and surfactants. The results demonstrated that the particle size, polydispersivity index, zeta potential, encapsulation efficiency and loading capacity of the SLNs were 154.72± 6.11nm, 0.42±0.11, -28.83±0.60mV, 59.66±3.22% and 6.13±0.32%, respectively. TEM and AFM images showed spherical to circular particles with well defined periphery. In vitro drug release exhibited biphasic pattern with an initial burst release of 18% within 2h followed by sustained release over 96h. FT-IR study suggested that during the process of formulations, lipid and surfactants have not reacted with the drug to give rise to reactant products and it was only physical mixture.